Conditional differential attacks on Grain‐128a stream cipher. (1st May 2017) - Ma, Zhen; Tian, Tian; Qi, Wen‐Feng
Abstract : The well‐known stream cipher Grain‐128a is the new version of Grain‐128. While Grain‐128 is vulnerable against several introduced attacks, Grain‐128a is claimed to be secure against all known attacks and observations on Grain‐128. So far the only published single‐key attack on Grain‐128a is the conditional differential cryptanalysis proposed by Michael Lehmann et al . at CANS 2012. In their analysis, a distinguishing attack on 189‐round Grain‐128a in a weak‐key setting was proposed. In this study, the authors present two new conditional differential attacks on Grain‐128a, i.e. attack A and attack B. In attack A, the authors successfully retrieve 18 secret key expressions for 169‐round Grain‐128a. To the best of our knowledge, attack A is the first attack to retrieve secret key expressions for reduced Grain‐128a. In attack B, the authors extend the distinguishing attack against Grain‐128a up to 195 rounds in a weak‐key setting. Thus far, attack B is the best known attack for reduced Grain‐128a as far as the number of rounds attacked is concerned. Hopefully, the authors' reflections on the design of Grain‐128a provide insights on such compact stream ciphers.